Measurement of the cross-section ratio [sigma][psi](2S)/[sigma]J/[psi](1S) in deep inelastic exclusive ep scattering at HERA - Abramowicz, Halina; Lisovyi, Mykhailo (Nuclear physics. B, Particle physics, 2016)
The exclusive deep inelastic electroproduction of ψ(2S) and J/ψ(1S) at an ep centre-of-mass energy of 317 GeV has been studied with the ZEUS detector at HERA in the kinematic range 2<Q2<80 GeV2, 30<W<210 GeV and |t|<1 GeV2, where Q2 is the photon virtuality, W is the photon-proton centre-of-mass energy and t is the squared four-momentum transfer at the proton vertex. The data for 2<Q2<5 GeV2 were taken in the HERA I running period and correspond to an integrated luminosity of 114 pb−1. The data for 5<Q2<80 GeV2 are from both HERA I and HERA II periods and correspond to an integrated luminosity of 468 pb−1. The decay modes analysed were μ+μ− and J/ψ(1S)π+π− for the ψ(2S) and μ+μ− for the J/ψ(1S). The cross-section ratio σψ(2S)/σJ/ψ(1S) has been measured as a function of Q2,W  and t. The results are compared to predictions of QCD-inspired models of exclusive vector-meson production.